Characterization and Initial Application of Endophytic Bacillus safensis Strain ZY16 for Improving Phytoremediation of Oil-Contaminated Saline Soils - Wu, Tao; Xu, Jie; Liu, Jian; Guo, Wei-Hua; Li, Xiao-Bin; Xia, Jiang-Bao; Xie, Wen-Jun; Yao, Zhi-Gang; Zhang, Yu-Miao; Wang, Ren-Qing (Frontiers in Microbiology, 2019)
Hydrocarbon-degrading and plant-growth-promoting bacterial endophytes have proven useful for facilitating the phytoremediation of petroleum-contaminated soils with high salinity. In this study, we identified Bacillus safensis strain ZY16 as an endophytic bacterium that can degrade hydrocarbons, produce biosurfactants, tolerate salt, and promote plant growth. The strain was isolated from the root of Chloris virgata Sw., a halotolerant plant collected from the Yellow River Delta. ZY16 survived in Luria-Bertani (LB) broth with 0–16% (w/v) sodium chloride (NaCl) and grew well in LB broth supplemented with 0–8% NaCl, indicating its high salt tolerance. The endophytic strain ZY16 effectively degraded C12–C32 n-alkanes of diesel oil effectively, as well as common polycyclic aromatic hydrocarbons (PAHs) under hypersaline conditions. For example, in mineral salts (MS) liquid medium supplemented with 6% NaCl, ZY16 degraded n-undecane, n-hexadecane, n-octacosane, naphthalene, phenanthrene, and pyrene, with degradation percentages of 94.5%, 98.2%, 64.8%, 72.1%, 59.4%, and 27.6%, respectively. In addition, ZY16 produced biosurfactant, as confirmed by the oil spreading technique, surface tension detection, and emulsification of para-xylene and paraffin. The biosurfactant production ability of ZY16 under hypersaline conditions was also determined. Moreover, ZY16 showed plant-growth-promoting attributes, such as siderophore and indole-3-acetic acid (IAA) production, as well as phosphate solubilization. To assess the enhanced phytoremediation of saline soils polluted by hydrocarbons and the plant-growth-promotion ability of ZY16, a pot trial with and without inoculation of the endophyte was designed and performed. Inoculated and non-inoculated plantlets of C. virgata Sw. were grown in oil-polluted saline soil, with oil and salt contents of 10462 mg/kg and 0.51%, respectively. After 120 days of growth, significant enhancement of both the aerial and underground biomass of ZY16-inoculated plants was observed. The soil total petroleum hydrocarbon degradation percentage (a metric of phytoremediation) after incubation with ZY16 was 63.2%, representing an elevation of 25.7% over phytoremediation without ZY16 inoculation. Our study should promote the application of endophytic B. safensis ZY16 in phytoremediation by extending our understanding of the mutualistic interactions between endophytes and their host plants.